Structural analysis of a large aluminum alloy truss double-arch bridge. (February 2021) - Wen, Qing-jie; Ren, Zi-jian
Abstract: In recent years, aluminum alloy bridges have been constructed in China, but a lack of aluminum alloy design and construction standards limits their further development. Traditional concrete and steel design theory cannot be completely adopted for aluminum alloy in large bearing structures. To introduce the structural design of a two-span continuous aluminum alloy truss arch bridge, this paper describes the material type, section design, component connections and bridge bearings in detail. Deflection and stress under live load are analyzed by means of a finite-element model to prove that the allowable deformation can be much greater than L /800 due to low stress in the members. Additional flexural stress subject to large eccentricity cannot be neglected, and the allowable joint eccentricity is proposed as 5% of the section height of the upper or lower chord, or about 15.0 mm. As a result of large ratio of live load to dead load, aluminum alloy footbridges reveal a rapid drop in frequency and pedestrian comfort when pedestrian mass is considered in the vibration analysis. Aluminum alloy footbridges are more sensitive to pedestrian mass than steel footbridges, and the comfort evaluation considering pedestrian mass is very necessary in design. Elastic buckling results reveal that steel and aluminum alloy footbridges have similar buckling modes, while aluminum alloy footbridges have lower buckling eigenvalue and ultimate bearing capacity. Furthermore, nonlinear buckling analysis of bridges is used to identify vulnerable members and improve structural stability by strengthening the local members. As a result, four rows of additional diagonal members near the middle pier were installed, and the elastic and nonlinear buckling bearing capacities reached 2.67 and 2.89 times the design pedestrian load, respectively. The additional diagonal web members were proved to play a significant role in increasing structural stability and evenly distributing the pedestrian load.